2019
DOI: 10.25289/ml.2019.8.2.50
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-level Light Therapy at 740 nm on Dry Eye Disease In Vivo

Abstract: Background and ObjectivesLow-level light therapy (LLLT) is an application of low-power light for various purposes such as promoting tissue repair, reducing inflammation, causing analgesia, etc. A previous study suggested the effect of light emitting diode (LED) light with the wavelength of 740 nm for promoting wound healing of corneal epithelial cells. This current study aimed to confirm the effect of LLLT for managing inflammation of a dry eye disease (DED) mouse model. Materials and MethodsA total of 50C57BL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
4
11
0
Order By: Relevance
“… 21 Unlike IPL, LLL has been shown to influence the lachrymal gland, for example, reducing the number of neutrophils or changing inflammatory cytokines in the lachrymal gland. 22 Additionally, LLL is the only treatment that was applied directly to the upper lid ( Table 1 ). The improvement in lipid layer thickness was frequently described in IPL without LLL treatment, 8 , 13 , 15 , 17 , 18 , 23 but other studies are showing no effect.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Unlike IPL, LLL has been shown to influence the lachrymal gland, for example, reducing the number of neutrophils or changing inflammatory cytokines in the lachrymal gland. 22 Additionally, LLL is the only treatment that was applied directly to the upper lid ( Table 1 ). The improvement in lipid layer thickness was frequently described in IPL without LLL treatment, 8 , 13 , 15 , 17 , 18 , 23 but other studies are showing no effect.…”
Section: Discussionmentioning
confidence: 99%
“…For immunohistochemistry, inflammatory cytokines interleukin-1 beta (IL-1β; ab9722; Abcam, Cambridge, MA, USA), interleukin-6 (IL-6; ab208113; Abcam) and tumor necrosis factor-alpha (TNF-α; ab6671; Abcam) were used to assess the level of inflammation in the collected tissues 7 .…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The treatment enhanced wound healing and improved patient satisfaction and wellbeing. The study [ 8 ] confirmed the photomodulation efficacy of low power DL radiation at 740 nm (previously proven to be effective in wound healing) for therapy of dry eye disease. The radiation can improve corneal surface, alleviate inflammation through decreasing of the neutrophils levels, etc.…”
Section: Introductionmentioning
confidence: 63%